Seni Patung Berbasis Teknologi Biner 01 - Lutse Lambert Daniel Morin (Ars: Jurnal Seni Rupa dan Desain, 2011)
Sculpture is three-dimensional works created as a way to communicate the artist to the recipient. In general, the sculpture has the look of  a close spatial relationship with the planning and preparation form. By some artists of  this digital technology is processed and used as a means of  creative media. Planning can form through the process without the process technology or technology-based aritmatic row that work based programming language. Blend series aritmatic 0 1 in binary processing will change analog data into an array of  data will produce the color through the liquid crystal display (LCD) or cathode ray tube (CRT). Analog data in the form sculpture sketch plan will be changed into electronic visual data displayed through the LCD or CRT screen.Keywords: Sculpture, Technology, Binary 0 1